Switchable Generation of Multipulse Patterns of Noise-Like Pulse and Dissipative Soliton Resonance in a Fiber Laser - He Xu; Sheng-Ping Chen; Yue Tao; Zong-Fu Jiang (IEEE Photonics Journal)
We report on the switchable generation of versatile patterns of multiple noise-like pulse (NLP) and dissipative soliton resonance (DSR) pulses in a dual-pump figure-eight mode-locked fiber laser. Benefiting from the change of saturation power influenced by pump power intercoupling, harmonic DSR pulses, dual-pulse DSR, dual-pulse and tri-pulse NLP are formed depending on different pump power combinations and intra-cavity polarization states. We find that the NLP pulse profile can turn from h-shape to triangular-shape after splitting. The dual-wavelength spectrum of the pulse, consisting of an obvious stokes line, can tune its center from 1075 to 1097 nm. This type of fiber laser may be helpful for further in-depth study on the underlying dynamics of multiple NLP and DSR pulses.